Imaging findings in diastematomyelia: A rare type of spinal dysraphism (Indian Journal of Case Reports, 2020)
Diastematomyelia, also termed as split cord malformation (SCM), is a rare congenital spinal dysraphism in which there is an abnormal sagittal clefting of the spinal canal that causes the cord to split into two hemicords by a fibrous, osseous, or cartilaginous septum. Various vertebral segmental anomalies such as hemivertebrae, butterfly vertebrae, and scoliosis are seen in association with diastematomyelia. Most of the diagnosed cases of diastematomyelia are children under the age of 7 years. Such a spinal anomaly is less frequently diagnosed in adults with female preponderance. We reported a case of diastematomyelia that was diagnosed by magnetic resonance imaging (MRI) in a 23-year-old woman who presented with chronic back pain for 7 years. MRI is the imaging modality of choice for establishing the diagnosis and exploring any associated malformations.